The impact on urban accessibility conditions of a proposed cableway line in the city of Manizales, Colombia - Montoya, Jorge Alberto; Aguilera, Juan Camilo; Escobar, Diego Alexander (Bulletin of Geography. Socio-economic Series, 2021)
Due to the tendency of Manizales and Villamaría population to use private transportation to mobilize in the urban environment, it is intended to include alternative modes of transport that are more efficient in a matter of time and environmentally sustainable to improve the quality of life of the inhabitants. This article aims to analyze the impact that the inclusion of a new line of cableway transportation system in the city that connects the central business district (CBD) with the North citadel commune by measuring global average accessibility, determining the savings it would generate in the population in terms of time.